Determinants of Students' Interest in Pursuing a Career: The Role of Financial Rewards as a Moderating Variable - Zaikin, Muhammad; Haliah, Haliah; Nirwana, Nirwana; Syamsuddin, Syamsuddin; Kusumawati, Andi (Pusat P2M Politeknik Negeri Batam, 2024)
Public accountants are very important to increase the credibility and transparency of financial information. This study was conducted to analyze the impact of professional recognition and labor market considerations on student interest in a career as an accountant with financial rewards as moderation. The population of this study amounted to 220 active accounting students class of 2021 at Halu Oleo University. Using purposive sampling technique, obtained 205 people as research samples. The results of the analysis found that professional recognition and labor market considerations affect students' interest in a career as an accountant. As a moderator, financial rewards can strengthen the influence of professional recognition and labor market considerations on student interest in a career as an accountant.